2010
DOI: 10.1590/s0100-55022010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Médicos e indústria farmacêutica: percepções éticas de estudantes de medicina

Abstract: INTRODUÇÃO: Após a Segunda Guerra Mundial, a indústria farmacêutica (IF) consolidou-se como importante e lucrativa atividade econômica. Considerando que os prescritores são médicos, a IF se vale de pesada campanha propagandística e do oferecimento de vantagens, desde os primórdios da formação médica. OBJETIVOS: Identificar percepções éticas em estudantes de Medicina no início do curso, além de comparar os distintos grupos que compõem a amostra. CASUÍSTICA E MÉTODOS: Estudo transversal, descritivo, baseado na a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Differently from the position of the authors previously analyzed [19][20][21] , M1 does not attribute to the media the responsibility of marketing for the sale of drugs, but rather to the industry itself, encouraging the media to present the drugs as a mere commodity. M1 relativizes a slang that penalizes representatives of industries as the sole responsible for introducing their products in the market, coopting the minds of prescribers in their networks.…”
Section: Pharmaceutical Industry and Medicinementioning
confidence: 87%
“…Differently from the position of the authors previously analyzed [19][20][21] , M1 does not attribute to the media the responsibility of marketing for the sale of drugs, but rather to the industry itself, encouraging the media to present the drugs as a mere commodity. M1 relativizes a slang that penalizes representatives of industries as the sole responsible for introducing their products in the market, coopting the minds of prescribers in their networks.…”
Section: Pharmaceutical Industry and Medicinementioning
confidence: 87%
“…It is widely known that the pharmaceutical industry has a huge economic impact worldwide, generating billions of dollars in revenue annually 1 , 8 . As part of the strategy to further increase their sales and profit, a considerable amount of money is spent on marketing to physicians, which includes pharmaceutical sales representative visits, sponsorship of conferences and other continuing medical education programs, drug promotional offers, free samples, and gifts 1 , 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, physician exposure to drug companies was found to be widespread worldwide. Previous studies from Brazil 8 , 10 , 18 and other countries such as Turkey 2 , Japan 3 , the United States 1 , and Germany 19 have shown that doctors and medical students frequently interact with the pharmaceutical industry, and a high percentage of them report having received small gifts, having attended drug company-sponsored events or meals, and even having scientific publication fees sponsored 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmaceutical industry therefore seeks out medical professionals to persuade them to prescribe a certain drug, and in return may offer some advantages. Obviously, one can find professionals who succumb to these advantages and thus start prescribing medicines despite the existence of alternatives of similar use or effect or appropriate cost 33, 34 .…”
Section: Discussionmentioning
confidence: 99%